Pedagogical and Psychological Aspects of Professional Sustainability of Future Teachers - Norkuzieva Manzura Abdurahmonovna (International Journal on Orange Technologies, 2021)
This article focuses on the issue of pedagogical-psychological approach in the professional adaptation of future teachers and ensuring its sustainability.